The accelerating rotation of the magnetic He-weak star HD 142990. Issue 4 (16th May 2019) - Shultz, M; Rivinius, Th; Das, B; Wade, G A; Chandra, P
ABSTRACT: HD 142990 (V 913 Sco; B5 V) is a He-weak star with a strong surface magnetic field and a short rotation period ( P rot ∼ 1 d). Whilst it is clearly a rapid rotator, recent determinations of P rot are in formal disagreement. In this paper, we collect magnetic and photometric data with a combined 40-yr baseline in order to re-evaluate P rot and examine its stability. Both period analysis of individual data sets and O − C analysis of the photometric data demonstrate that P rot has decreased over the past 30 yr, violating expectations from magnetospheric braking models, but consistent with behaviour reported for 2 other hot, rapidly rotating magnetic stars, CU Vir and HD 37776. The available magnetic and photometric time series for HD 142990 can be coherently phased assuming a spin-up rate$\dot{P}$ of approximately −0.6 s yr −1, although there is some indication that$\dot{P}$ may have slowed in recent years, possibly indicating an irregular or cyclic rotational evolution.